2020
DOI: 10.3390/ijms21228676
|View full text |Cite
|
Sign up to set email alerts
|

Digital Image Analysis Applied to Tumor Cell Proliferation, Aggressiveness, and Migration-Related Protein Synthesis in Neuroblastoma 3D Models

Abstract: Patient-derived cancer 3D models are a promising tool that will revolutionize personalized cancer therapy but that require previous knowledge of optimal cell growth conditions and the most advantageous parameters to evaluate biomimetic relevance and monitor therapy efficacy. This study aims to establish general guidelines on 3D model characterization phenomena, focusing on neuroblastoma. We generated gelatin-based scaffolds with different stiffness and performed SK-N-BE(2) and SH-SY5Y aggressive neuroblastoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Based on higher cluster and VN Frontiers in Cell and Developmental Biology frontiersin.org integrated densities, together with increased degradation of the stiff hydrogels, we infer that 3 wt% VN/PEG conditions better recreate NB cell behavior. However, cell adaptive response depends on stiffness, time and the genetic background of the cell line, as previously suggested in the literature (López-Carrasco et al, 2020;Monferrer, Sanegre, et al, 2020), so further genetic and drug-testing studies on long-cultured models, using various MYCN amplified and/or ALK mutated NB cell lines, should be performed to confirm which model better recapitulates high-risk NB behavior. Finally, VN synthesis even in VN rich ECM conditions strengthen the relevance of testing VN targeted preclinical therapies in NB.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Based on higher cluster and VN Frontiers in Cell and Developmental Biology frontiersin.org integrated densities, together with increased degradation of the stiff hydrogels, we infer that 3 wt% VN/PEG conditions better recreate NB cell behavior. However, cell adaptive response depends on stiffness, time and the genetic background of the cell line, as previously suggested in the literature (López-Carrasco et al, 2020;Monferrer, Sanegre, et al, 2020), so further genetic and drug-testing studies on long-cultured models, using various MYCN amplified and/or ALK mutated NB cell lines, should be performed to confirm which model better recapitulates high-risk NB behavior. Finally, VN synthesis even in VN rich ECM conditions strengthen the relevance of testing VN targeted preclinical therapies in NB.…”
Section: Discussionmentioning
confidence: 85%
“…In particular, our previous results highlighted VN as a relevant glycoprotein related to NB patients with poor prognosis (Burgos-Panadero, Vicente-Munuera et al, 2020). Our previous results with a clinical cohort and preclinical models (orthotopic xenograft VN knock-out (KO) mice and 3D bioprinted hydrogels with different stiffness) have also established that the interaction of VN, its ligands (e.g., αv integrins), and genomic intratumor heterogeneity in MYCN-amplified NB cell line are related to increased ECM stiffness (Burgos-Panadero, López-Carrasco et al, 2020;Monferrer, Sanegre, et al, 2020;Vicente-Munuera et al, 2020). Furthermore, we performed preclinical therapeutic studies on NB monolayer cell cultures, targeting VN function blockade by employing cilengitide (αv integrin antagonist) and combination therapy with etoposide-loaded (cytotoxin used in high-risk NB treatment) lipid nanoparticles (Burgos-Panadero et al, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, cells in vivo may not only receive signals on one side but also receive signals from all directions (Baker and Chen, 2012). Therefore, cell migration is considered to be different in dimensionality (Rebelo et al, 2018;Young et al, 2018;Monferrer et al, 2020). The scratch assay is typically used to measure basic cell migration parameters such as speed, persistence and polarity.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, our group has previously described a common aggressive pattern of rigid ECM in HR-NB [14], rich in cross-linked collagen III fibres, poor in glycosaminoglycans, supporting sinusoidal vascular structures (blood and lymphatic) and with a high amount of territorial vitronectin (located in cytoplasmic compartments and a thin layer around tumour cells) [15][16][17][18]. In a recent study we observed the dramatic impact of ECM stiffness on ITH and clonal evolution of a MNA NB cell line, in which dominant clones were selected when cultured in stiff 3D-bioprinted hydrogels and in xenograft tumours; these changes were not found in an ALK mutated NB cell-line [3,19]. A continuous interplay therefore exists between TME and genetics, tumour cell proliferation, aggressiveness and migration [20].…”
Section: Introductionmentioning
confidence: 99%